Из наблюдений над способами выражения отрицания в церковнославянском тексте русского извода - Zofia Szwed (Studia Rossica Posnaniensia)
The article describes the specificity of the changes that took place in the process of dissemination of double negation, typical for Slavic languages, visible in the Ruthenian recension of Church Slavonic texts. The reflections on the achievements in the field are enriched with the results of research on the text of Gospel No. 7 from the collection of the Russian State Archive of Ancient Acts (RGADA F. 381. Op. 1 Unit hr 7), which has not been analyzed so far in terms of the issues raised. Nearly three hundred negative structures were subjected to observations. In order to determine the number of single negation cases in relation to double negation the main focus was on structures such as: (1) ni Pron + V, (2) ni Pron + ne V oraz (3) ne V + ni Pron. It was determined, among other things, that their use was influenced by both the literature tradition and live language with elements of the northern dialect of the East Slavonic. On the other hand, the analysis of the negative structures preceding homogeneous parts of the sentence revealed the tendency, manifested on the leaves of the monument, to transform towards the norm of the contemporary Russian language.